Comparison of Mifepristone plus Misoprostol with Misoprostol alone for First Trimester Medical Abortion: A Systematic Review and Meta-Analysis Protocol: Comparison of Mifepristone plus Misoprostol with Misoprostol Alone for First Trimester Medical Abortion - Shimels, Tariku (Ethiopian Journal of Reproductive Health, 2022)
Objective: The objective of this review is to compare mifepristone plus misoprostol combined regimen with misoprostol alone in medical abortion of first trimester pregnancy. Introduction: Original clinical trials have demonstrated that the combined mifepristone plus misoprostol has a marked effectiveness on first trimester abortion practices compared to the misoprostol alone regimen. However, there is no clear evidence if this effect holds consistent direction for all main outcomes and, whether subsequent complications or side effects are minimal or not. This review is intended to provide aggregated evidence for this question through comparison of the respective regimens based on findings from previous randomized control trial studies. Inclusion criteria: Randomized control trials which compared mifepristone plus misoprostol with misoprostol alone for first trimester medical abortion and published in English language will be included in the review. Articles attempted to evaluate procedures and mechanisms of first trimester abortion other than mifepristone plus misoprostol combined regimen with misoprostol alone will be excluded. Methods: An internet based search of different engines will be undertaken to identify articles on the proposed topic. Using text words contained in the titles and abstracts of relevant articles, a full search of PubMed/Medline, Cochrane CENTRAL, EMBASE, WHO international clinical Trial registry platform and google scholar will be made. We used English based articles published earlier to April 2019 on human subjects as a search limit. Studies which fulfil the inclusion criteria will be selected, appraised and assessed for methodological quality by two independent reviewers. Data on participants, study methods, interventions, and outcomes will be abstracted. Included studies will be pooled for meta-analysis. Results will be reported in odds or risk ratio at 95% confidence interval.